ANALISIS ON-TIME PERFORMANCE SEBAGAI UPAYA MENGAWASI KUALITAS MENGGUNAKAN METODE DIAGRAM KONTROL DAN MENINGKATKAN KUALITAS JASA MENGGUNAKAN METODE PARETO CHART DAN DIAGRAM SEBAB-AKIBAT (Studi Pada PT. Sriwijaya Air) - Arifianto, Mohammad Yogi; Munas Dwiyanto, Bambang (Faculty of Economics and Business Diponegoro University, 2013)
On-time Performance is a crucial factor in the airlines. PT. Sriwijaya Air as the object of this research, shows low On-time Performance on January 2012 until March 2013. It did not reached the company’s predetermined On-time Performance target. This research is intended to seek the root cause of low on-time performance so that Sriwijaya Air can focus on the major cause for conducting repairs.The methods used in this study consists of three quality tools; Control Chart, Pareto Chart, and Cause and Effect Diagram. The use of Control Chart is to see the problem occurring at a specific time. Afterwards, the use of Pareto Chart is to define the primary problems and focuses the attention towards the problems. Lastly, the use of Cause and Effect Diagram is to find the root causes from the primary problems.The result defined three main causes that cause delay on PT. Sriwijaya Air and those are; Flight Crew, Service, and Technical. The Cause and Effect Diagram found the root causes of the problem and the results shows that the problem is in the flight activity procedures. The three main problems are classified as an internal factor delay. Therefore some actions to remedy these delays need to be taken.